Effect of monocalcium phosphate supplementation on the growth performance, carcass characteristic, gut histomorphology, meat and bone quality of broiler chickens - Lim, Eric Teik Chung; Kamalludin, Mamat Hamidi; Abdullah, Faez Firdaus Jesse; Reduan, Mohd Farhan Hanif; Loh, Teck Chwen; Idrus, Zulkifli (Universiti Putra Malaysia Press, 2019)
The aim of this study was to investigate the effect of different concentration of monocalcium phosphate supplementation on the growth performance, carcass characteristics, gut morphology, meat quality, and bone quality of broiler chickens. A total of 108 day-old male broiler chicks (Cobb 500) were randomly divided into 3 treatment groups with 6 replicates and each replicate consist of 6 birds. Treatment 1 (control) was fed available commercial starter and finisher diets containing dicalcium phosphate. Treatment 2 and Treatment 3 were fed the same commercial diet but with added 0.5% and 1.0% of monocalcium phosphate respectively. Weekly body weight, feed intake and feed conversion ratio were calculated to determine their growth performance. A total of 12 chickens per each treatment group were selected randomly and slaughtered for gut histomorphology, carcass characteristics, meat, and bone quality assessment at the end of the 42 days study period. In the present study, birds supplemented with 0.5% MCP showed significant increase (p > 0.05) in growth performance (body weight, body weight gain, and feed intake), gut histomorphology (villi height), and bone quality (bone weight, diaphysis diameter, medullary canal diameter, lateral wall thickness, medial wall thickness, and bone breaking strength). There were no significant differences (p > 0.05) in the carcass characteristics and meat quality between treatment groups. In summary, monocalcium phosphate supplementation could be the key to reduce culling of lame broiler birds based on the positive effect on the growth performance, gut histomorphology and bone quality of broiler chickens without affecting the carcass characteristics and meat quality.